Legal Orientalism: CHINA, THE UNITED STATES, AND MODERN LAW - Teemu Ruskola (Harvard University Press, 2013)
LAWâ€™S ORIENT CONSTITUTES a wide and uneven terrain. Th is book describes the itinerary of one par tic u lar journey across that terrain, with a focus on China and the United States. Law is a key aspect of the po liti cal ontology of the modern world. It is exceedingly diffi cult, if not impossible, for us to think of politics outside of the framework of states, and of states outside of law. At the same time, no understanding of the world today is complete without consideration of Chinaâ€™s place in it. Th e diffi culties begin when we seek to combine the inquiries into law and China. Where is China in lawâ€™s world? And why is the United States an important part of the answer to that question? If there is one image of China that is seared in the collective consciousness of the West, it is that of a solitary man facing a tank in Tiananmen Square on June 4, 1989. Indeed, after the end of the Cold War and the roughly contemporaneous massacre by the Chinese government of its own citizens, China has come to occupy the role of the leading human rights violator in the Eastâ€” a position left vacant by the collapse of the USSR. While the Peopleâ€™s Republic of China (PRC) has by now secured itself a solid reputation as a law breaker in chief, the United States has emerged as the worldâ€™s chief law enforcer as well as its leading law exporter, administering programs for the promotion of rule- of- law everywhereâ€” and perhaps nowhere as vigorously as in China. Th is book starts from the premise that the complex and unstable relationship among China, the United States, and legal modernity is of utmost global signifi cance. To map that relationship, it analyzes law as a fundamental element in the modern worldview that conceives the individualâ€” the singular human beingâ€” as the paradigmatic existential, po liti cal, and legal subject and the state as the privileged medium for the instantiation of its universal values, through law. More than just a set of rules for regulating behavior, law in this larger sense is a structure of the po liti cal imaginationâ€” â€œa distinctive manner of imagining the real,â€ in Cliff ord Geertzâ€™s words. One of its most important imagined Others is the Orient, and legal Orientalism is the discourse in which it is imagined.